Dexmedetomidine Combined With Butorphanol or Sufentanil for the Prevention of Post-operative Nausea and Vomiting in Patients Undergoing Microvascular Decompression: A Randomized Controlled Trial - Xu, Guangjun; Zhao, Jing; Liu, Zunyuan; Liu, Guoying; Liu, Lei; Ren, Chunguang; Liu, Yanchao (Frontiers in Medicine, 2020)
Background: Patients undergoing microvascular decompression are often accompanied with high risk of postoperative nausea and vomiting (PONV). In this study, we compare the antiemetic efficacy of butorphanol or sufentanil combined with dexmedetomidine in patients undergoing microvascular decompression. Methods: Patients undergoing microvascular decompression were randomized into two groups. The primary outcome was the occurrence and severity of postoperative nausea and vomiting during the 72 hours after surgery. Secondary outcomes included levels of pain intensity and sedation, consumption of opioids at time of 1, 2, 6, 12, 24, 48 and 72 hours after surgery. We also recorded the intraoperative hemodynamics, consumption of narcotic drugs, operation and anesthesia time, estimated blood loss, infusion volume and urine output, requirements of rescue antiemetics or analgesics, the satisfaction scores of patients and surgeons complications and length of stay. Results: The overall incidence rates of nausea and vomiting during the 72 hours after surgery were significantly reduced in group DB (76.00% and 44.00% in group DS vs. 54.17% and 22.92% in group DB, P < 0.05). Patients in group DB had a lower incidence of nausea than group DS at intervals of 1–6 hours and 6–24 hours (P < 0.05). However, patients in group DB had a lower incidence of vomiting than group DS only at intervals of 1–6 hours (P < 0.05). Similarly, patients required rescue antiemetics were also significantly reduced in group DB than that of group DS at intervals of 1–6 hours (P < 0.05). The number of patients experienced moderate to severe PONV was comparable between the two groups during 72 hours after surgery (P > 0.05). The consumption of opioid morphine equivalent was significantly reduced in group DB (P < 0.05). Compared with group DS, the satisfaction scores of both patients and surgeons were significantly increased in group DB (P < 0.05). Conclusion: Butorphanol combined with Dexmedetomidine could reduce early PONV and the number of patients required rescue antiemetics, especially at intervals of 1–6 hours, while the satisfaction scores of both patients and surgeons were significantly increased.